Effective catalytic hydrodechlorination of chlorophenoxyacetic acids over Pd/graphitic carbon nitride1. Issue 64 (12th July 2015) - Jiang, Fang; Tan, Wenhui; Chen, Huan; Tan, Ling; Liu, Jingliang
<x xml:space="preserve">Abstract</x> Catalytic hydrodechlorination (HDC) of chlorophenoxyacetic acids was performed over Pd/graphitic carbon nitride (Pd/g-C3N4) catalysts in the present work.